Risk Factors Associated with Cardioembolic Stroke in Patients with non Valvular Atrial Fibrillation - Daniel Guerra García; Francisco Valladares Carvajal; Ernesto Julio Bernal Valladares; José Aurelio Díaz Quiñones (Universidad de las Ciencias Médicas de Cienfuegos, 2018)
Foundation: atrial fibrillation is the most frequent arrhythmia treated in the clinical practice and the one which causes 33 % of hospital admissions. Morbimortality increases significantly with the risk of stroke and cardiac failure. Objective: to identify the risk factors associated to the onset of cardioembolic stroke in patients with atrial fibrillation and cardiac failure. Methods: descriptive correlational study of two series of cases, Group A (patients with diagnosis of atrial fibrillation and cardioembolic stroke and Group B (patients with diagnosis atrial fibrillation without cardioembolic stroke). These cases came to outpatient consultation of arrhythmias or were admitted to the stroke unit at the Cienfuegos Dr. Gustavo Aldereguía Lima from November 2014 to July 2016. A number of 103 patients were studied, 50 with atrial fibrillation and cardioembolic stroke and 53 with atrial fibrillation without cardioembolic stroke. Demographic variables as age and sex and clinical variables; toxic habits, comorbidities, therapeutic management with anticoagulants and ecocardiographic variables were analyzed. Results: patients with atrial fibrillation without cardioembolic stroke increased in relation to aging. The most important co/morbidity was arterial hypertension; there was a low number of patients treated with anticoagulants before stroke and statistic association of the number of risk factors with the onset of stroke. Conclusion: the identified risk factors for cardioembolic stroke in patients with atrial fibrillation were age, arterial hypertension and stroke previous anticoagulant treatment and the coexistance of more than two known risk factors.